LEGAL STATUS OF SUBJECTS OF POWER: DOCTRINAL APPROACH - Dmitriev, Ihor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the article is devoted to the legal status of the subject of power. The aim of the article is to study the doctrinal approach to understanding the essence of the definition of «legal status of the subject of power», improving the categorical apparatus of legal regulation of relations in which the participants are the subjects of power. Research methods: general philosophical, general scientific and special legal methods, in particular dialectical method, method of analysis, system-functional method, formal-logical method, hermeneutic method. Results: through the analysis of the current legislation revealed the absence in the regulations that provide legal regulation of the legal status of the subjects of power, the definition of the concept under study. Emphasizes the lack of relevant scientific developments. Discussion: on the basis of the data received during the analysis of the corresponding legislative provisions, scientific and theoretical base, the author’s definition of definition «legal status of the subject of power» under which it is offered to understand set of special rights is developed, The subjects of power include: the Verkhovna Rada of Ukraine; President of Ukraine; Cabinet of Ministers of Ukraine; central executive bodies; bodies of the Prosecutor’s Office of Ukraine; other central bodies of state power and state institutions that do not belong to the system of executive bodies; authorities of the Autonomous Republic of Crimea representedи ministries and republican committees; local executive bodies operating at the level of oblasts, cities of Kyiv and Sevastopol, as well as districts; territorial representations (main departments, divisions, etc.) of central executive bodies (for example, the Main Department of Justice in Kyiv region, Main Department of the Ministry of Internal Affairs of Ukraine in the Donetsk region, etc.) and public authorities (institutions) that do not belong to the system of executive authorities; judicial authorities; local governments; subsidiary (advisory) bodies; other legal entities under public law; officials and officials of public authorities, local governments, other legal entities under public law; subjects of delegated powers.